2019
DOI: 10.1177/0963689719884885
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation with GXHPC1 for Liver Cirrhosis: Phase 1 Trial

Abstract: Currently, the only effective therapy for cirrhosis of the liver is liver transplantation. However, finding a compatible liver is difficult due to the low supply of healthy livers and the ever-increasing demand. However, stem-cell therapy may offer a solution for liver cirrhosis; for example, GXHPC1 therapy preparation contains adipose-derived mesenchymal stem cells (AD-MSCs) and was developed for the treatment of liver cirrhosis. In our previous report, animal studies suggested that treatment of a diseased li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In these trials, ADSC transplantation did not raise any safety concerns. Besides, tests that measure liver function, such as the 13 C methacetin breath test, METAVIR score, Child-Pugh score, and MELD score, have yielded positive results [ 160 , 161 ]. Combined, these findings suggest that ADSC transplantation is a promising therapeutic option for the treatment of liver injury.…”
Section: Regenerative Medicine Based On Adscsmentioning
confidence: 99%
“…In these trials, ADSC transplantation did not raise any safety concerns. Besides, tests that measure liver function, such as the 13 C methacetin breath test, METAVIR score, Child-Pugh score, and MELD score, have yielded positive results [ 160 , 161 ]. Combined, these findings suggest that ADSC transplantation is a promising therapeutic option for the treatment of liver injury.…”
Section: Regenerative Medicine Based On Adscsmentioning
confidence: 99%
“…Existing studies have shown that MSC therapy is prominently effective in hepatic fibrotic diseases indirectly by regulating the immune metabolism microenvironment (El Agha et al, 2017). The secretion of IL-17A from Th17 cells can promote fibrosis by activating fibroblasts (Huang et al, 2019;Hu et al, 2020). BM-MSCs inhibited liver fibrosis by decreasing the expression of IL-17A and IL-17RA and the serum levels of IL-17 in the liver (Farouk et al, 2018).…”
Section: Therapies Targeting the Hif Pathway To Alleviate Fibrosismentioning
confidence: 99%
“…The Laennec fibrosis scoring analysis following transplantation revealed that histological improvements were observed in 54.5% patients given 5 × 10 7 MSCs with 2 separate infusions and 4 weeks apart [ 112 ]. Similarly, clinical trials also showed that autologous BM-derived MSC administration reduced histological fibrosis and improved liver function in those patients with alcoholic cirrhosis [ 113 , 114 ]. Consequently, BM-derived MSC treatment can be a suitable option for fibrosis reduction and recovery from liver injury in patients with alcoholic cirrhosis.…”
Section: Clinical Applications Of Autologous Vs Allogeneic Mscsmentioning
confidence: 99%